Contribution to the analysis of certain technological aspects of soft wheat seeds treated with purified wastewater. - Dr Nadia CHIAHI; Dr Messaouda REZAGUI (Islamic Azad University, 2024)
Our objective in this study was first to evaluate the technological quality of soft wheat treated with purified wastewater. In the second phase, we aimed to study and compare various physiological and biochemical parameters of two soft wheat varieties (Triticum aestivum L.), El-Hiddab (HD1220) and Béni Sélimane (ARZ), irrigated with either rainwater or purified wastewater. According to our findings, the use of purified wastewater is beneficial for technological parameters such as moisture, ash, gluten, and chlorophyll content in soft wheat. The analytical results of our experiments largely comply with national standards.
Technological Insights on Soft Wheat Seeds Treated with Purified Wastewater.
Keywords: soft wheat; irrigation; purified wastewater; technological parameters; viability and vigor; accelerated aging